2010
DOI: 10.1128/iai.00295-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Conserved Group A Streptococcal Proteins Identified by the Antigenome Technology as Vaccine Candidates for a Non-M Protein-Based Vaccine

Abstract: Group A streptococci (GAS) can cause a wide variety of human infections ranging from asymptomatic colonization to life-threatening invasive diseases. Although antibiotic treatment is very effective, when left untreated, Streptococcus pyogenes infections can lead to poststreptococcal sequelae and severe disease causing significant morbidity and mortality worldwide. To aid the development of a non-M protein-based prophylactic vaccine for the prevention of group A streptococcal infections, we identified novel imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 67 publications
1
69
1
Order By: Relevance
“…In Streptococcus pyogenes, Spy1356, the SepM homolog, has multiple functions. Spy1356 is crucial for surface expression of various proteins, including M protein, and responsible for binding with the extracellular matrix proteins (13). Further studies are necessary to unravel the range of processes regulated by SepM and its homologs in other Grampositive organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Streptococcus pyogenes, Spy1356, the SepM homolog, has multiple functions. Spy1356 is crucial for surface expression of various proteins, including M protein, and responsible for binding with the extracellular matrix proteins (13). Further studies are necessary to unravel the range of processes regulated by SepM and its homologs in other Grampositive organisms.…”
Section: Discussionmentioning
confidence: 99%
“…SepM processes synthetic CSP. SepM is predicted to be a membrane-associated protein, and its ortholog in group A streptococcus (GAS) is localized on the surface (13,47). Since a putative Lon-like protease domain is encoded within the sequence, we speculated that SepM might be involved in the postexport maturation of CSP-21.…”
Section: Fig 2 Effect Of Synthetic Csp On Pnlma Expression and Transfmentioning
confidence: 99%
“…Demonstrating the robustness of this technology, SpyCEP has been identified as a protective GAS antigen in multiple studies employing GAS reverse vaccinology (582,587,588). One such study used trypsin to "shave" surface-exposed proteins, which were subsequently identified by proteomics (588).…”
Section: Gas Reverse Vaccinologymentioning
confidence: 99%
“…Therefore, the development of efficacious vaccines against obligate and facultative intracellular pathogens depends largely upon the ability to identify antigen formulations that induce effective B-and T-cell responses (1)(2)(3). Although both genomic and proteomic strategies have been applied successfully to discover B-cell-stimulating vaccines (4)(5)(6)(7), the identification of antigens eliciting effector T cells generally is considered less amenable to high-throughput approaches.…”
mentioning
confidence: 99%